2013
DOI: 10.1371/journal.pone.0079992
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Kidney Function by Dynamic Contrast Enhanced MRI and FITC-Sinistrin Clearance in Rats at 3 Tesla: Initial Results

Abstract: Glomerular filtration rate (GFR) is an essential parameter of kidney function which can be measured by dynamic contrast enhanced magnetic resonance imaging (MRI-GFR) and transcutaneous approaches based on fluorescent tracer molecules (optical-GFR). In an initial study comparing both techniques in separate measurements on the same animal, the correlation of the obtained GFR was poor. The goal of this study was to investigate if a simultaneous measurement was feasible and if thereby, the discrepancies in MRI-GFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Early functional changes have previously been investigated in several models of ischemia reperfusion AKI following the administration of Gd‐based contrast agents. Most of these studies addressed the quantification of renal perfusion and estimation of glomerular filtration rate both at preclinical and clinical levels . DCE‐MRI methods are less time consuming and costly than methods based on the clearance of injected tracers, and do not involve radiation issues, as in radionuclide renography .…”
Section: Discussionmentioning
confidence: 99%
“…Early functional changes have previously been investigated in several models of ischemia reperfusion AKI following the administration of Gd‐based contrast agents. Most of these studies addressed the quantification of renal perfusion and estimation of glomerular filtration rate both at preclinical and clinical levels . DCE‐MRI methods are less time consuming and costly than methods based on the clearance of injected tracers, and do not involve radiation issues, as in radionuclide renography .…”
Section: Discussionmentioning
confidence: 99%
“…One of them is the independence from blood and urine sampling which leads to great savings in terms of consumables, time and, of course, animal stress. Table 2, the exogenous renal marker FITC-sinistrin and the measurement of its elimination kinetics through the skin allow the impact of renal pathologies on kidney function to be studied 9,10,[14][15][16][17][18] . The serial collection of blood samples required to assess plasma clearance or biomarkers of renal disease are stressful for the animal, cumbersome and time-consuming for the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The approach has some limitations, since it requires almost complete immobilization during the procedure, which in animals usually requires an anesthetic. This may result in errors in GFR estimation, as shown by Zöllner et al [35]. Their findings demonstrated that the mean GFR values determined in rats using MRI were about half those found through transcutaneous FITC-sinistrin clearances.…”
Section: Discussionmentioning
confidence: 97%